METODE DAKWAH BIL-HIKMAH KIAI HAJI HASYIM ASY’ARI DALAM FILM SANG KIAI : ANALISIS SEMIOTIKA ROLAND BARTHES - Lailatul Aini; Nur Ainiyah (Maddah : Jurnal Komunikasi dan Konseling Islam, 2026)
This study examines the representation of K.H. Hasyim Asy'ari's da'wah bil-hikmah method in the film Sang Kiai (2013) by Rako Prijanto. Da'wah bil-hikmah is understood as a da'wah approach that emphasizes wisdom, exemplary behavior, and persuasive communication in accordance with the social context. This study uses a descriptive qualitative approach with Roland Barthes's semiotic analysis to identify the denotative, connotative, and mythical meanings that represent the practice of da'wah bil-hikmah in the film's storyline, characters, and moral message. The results show that the film Sang Kiai represents K.H. Hasyim Asy'ari as a scholar and leader who implements da'wah bil-hikmah through four main approaches: wisdom in taking action, gentle persuasion, moral example, and utilizing social and cultural contexts as a means of da'wah. These findings confirm that film can function as an effective da'wah medium in conveying Islamic values in a contextual and moderate manner.